2014
DOI: 10.1002/tee.22039
|View full text |Cite
|
Sign up to set email alerts
|

Relation between plasma plume charge and length in atmospheric pressure plasma

Abstract: We present atmospheric pressure plasma generated using a quartz tube, helium gas, and copper foil electrode by applying a radio frequency high voltage. The atmospheric pressure plasma in the form of a bullet is released as a plume into the atmosphere.To study the formation of the plasma plume, the dependences of the plasma plume charge and the plasma plume length on the gas flow rate are examined. In a quartz tube with inner diameter 1.5 mm, which has more helium than air in the cross section of the flow chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The gas flow is controlled by a gas mass flow controller. The AC power supply (LHV‐13A, Logy Electric) can deliver a voltage from −6 to +9 kV and a main frequency of about 13 kHz, and the usual waveform is an asymmetric sine wave about the ground line .…”
Section: Methodsmentioning
confidence: 99%
“…The gas flow is controlled by a gas mass flow controller. The AC power supply (LHV‐13A, Logy Electric) can deliver a voltage from −6 to +9 kV and a main frequency of about 13 kHz, and the usual waveform is an asymmetric sine wave about the ground line .…”
Section: Methodsmentioning
confidence: 99%
“…Fluid dynamic analysis. While fluid dynamic properties of atmospheric pressure plasma-jets [35][36][37][38][39] and buoyant helium jets 40,41 have been studied previously, the laminar and turbulent flow regions of the PJP have not been evaluated for determining ideal deposition parameters. It has been shown that the voltage and helium fluid velocity play a significant role in the length of the plasma plume.…”
Section: Nanoscale Papermentioning
confidence: 99%
“…As a result, less charge is expected to accumulate with the double DBD configuration [23]. These accumulated charges could induce higher electric field resulting in the longer length of the plasma plume (figure 2) and could also increase the chemical reactivity of the plasma [24].…”
Section: Plasma Plume Lengthsmentioning
confidence: 99%